The value of different recycling technologies for waste rubber tires in the circular economy—A review - Goevert, Dennis (Frontiers in Sustainability, 2024)
The issue of used rubber tires is becoming an ever-greater problem for the environment. Often these are disposed of in an illegal manner. Whether on forest paths, fields, or other unsuitable areas -illegal disposal of used tires is a punishable offense and a risk to people and the environment. Nevertheless, the number of cases increases from year to year. This is partly caused by the lack of suitable recycling options for waste tires. Reuse does take place but mainly in the form of downcycling, with the majority currently either being incinerated for energy recovery or, as shredded tires, used as substrate or filler material in roads and sporting grounds. Several reclamation technologies have been developed in the past, using for example mechanical, thermal energy and/or chemicals, aiming to provide a better solution to the waste tire problem, however, most processes cause some form of rubber degradation that limits reuse to low value applications. Only devulcanisation using a biotechnological approach with microorganisms and/or enzymes shows currently promise to reuse waste rubber for high value applications such as new tires. This review provides an overview of the technological development of different recycling options and their potential benefit to the circular economy. Deleted: The challenges of reusing waste rubber and 36 potential biotechnological solutions 37 This is a provisional file, not the final typeset article 4.5 Reclamation using supercritical CO2 .